An evaluative study of participatory development: the dynamics of rural community develoment in Sarawak - Debataraja Mamora, Tagor Toman (2025)
Participation and communication are key terms in the study, and they work in tandem. They raise the need for dialogic communication and collaborative activities to foster empowerment and greater interaction for the villagers of Kampung Opar and Sebauh longhouses, the sites of my research, so that they can assert their role in community development planning and decision making. With development policy and implementation generally taking a top-down approach, politics and power relations remain a powerful factor of influence, limiting the social space for freely occurring group or community-initiated participatory activities.